Curva de embebição, anatomia e mobilização de reservas em sementes de Mimosa flocculosa Burkart submetidas a superação de dormência - Ribeiro, Maiara Iadwizak (2019)
Our study aimed to expand the knowledge in Mimosa flocculosa seed physiology and overcome dormancy treatments efficiency, focusing on water uptake, reserves mobilization, integument anatomy and seed germination. For the hydration curve, we tested three different treatments: distilled water (control), water at 80 °C for 10 min and sulfuric acid for 3 min, each containing four replicates of 100 seeds. Seeds were placed in Germitest papers, moistened with distilled water and stored in germination chambers. To obtain fresh mass, seeds were weighted in a precision scale. From the hydration curve data, we stipulated 5 points to collect material for reserves mobilization quantification: beginning of hydration, middle of phase I, phase II, middle of phase II and beginning of phase III. Total soluble sugars, reducing sugars, sucrose, albumines, globulines, prolamines, and glutelines were quantified. The beginning of each phase was used to observe the alterations in M. floculosa integumentary seed anatomy. Germination tests were prepared in parallel with the hydration curve, in which were analyzed: germination percentage, relative frequency and synchrony of germination. We noticed that, comparing with the control, overcome dormancy treatments are indicated to improve seed germination, since germination was more uniform, sugars and proteins were more reduced during hydration, integument presented fissures and destabilization, ensuring water uptake, improving seed germination and synchrony.